Seasonal influence on dormancy alleviation in Dodonaea viscosa (Sapindaceae) seeds. Issue 3 (September 2014) - Jaganathan, Ganesh K.; Liu, Baolin
Abstract Seeds of Dodonaea viscosa (Sapindaceae) have a water-impermeable seed coat, i.e. physical dormancy (PY). Although mechanical scarification, dry heat, sulphuric acid and hot water treatment make seeds permeable under laboratory conditions, the mechanisms by which dormancy is alleviated in natural environments have not yet been understood completely. The present investigation aims to understand the pattern of dormancy alleviation in D. viscosa seeds using an artificial burial approach for 2 years. Freshly collected seeds held in hydrated soil at 10/20°C, 15/20°C, 15/30°C, 20/35°C and 25°C for 32 weeks germinated to less than 15%, irrespective of storage temperature. Dry storage of seeds at 15, 20, 25 and 30°C for 1 year did not break dormancy. Hot water treatment at 80 and 90°C for 30 s broke dormancy in 90% of the seeds. On the other hand, burying seeds at a depth of 3–5 cm in the natural environment for 2 years increased germination from 7 to 71%. In particular, seeds exhumed after summer in both years showed a significant increase in germination percentage (P< 0.05). However, seeds buried after summer did not germinate to a higher percentage when exhumed prior to summer. We suggest that a high summer temperature, rising above 60°C in the top soil layer of the tropics, is a likely factor breaking dormancy. Most seeds germinated during burial, which indicates that light is not a cue for germination. We conclude that germination of D. viscosa following summer is an adaptive mechanism to tolerate summer droughts, which are common in the dry tropics.